Selective correlation of hippocampal volumes with WADA memory scores in mesial temporal sclerosis patients - Lourdes Khalife; Wassim Nasreddine; Fatima Jaafar; Huda Abboodi; Karim Nasreddine; Ahmad Beydoun (Frontiers in Neurology)
ObjectiveThe WADA test is used to determine cerebral language dominance and assess the risk of postoperative amnesia following mesial temporal lobe resection. This study aims to explore the correlation between automated measures of hippocampal volume and WADA memory scores and to evaluate whether these volumetric measurements can reliably predict WADA memory scores.MethodsThis study included patients who underwent a comprehensive presurgical assessment along with bilateral WADA testing. Hippocampal volumes were measured from high-resolution brain MRIs using automated software (volBrain), which were harmonized and normalized to whole brain volume. These harmonized and normalized volumes were then correlated with ipsilateral WADA memory scores and stratified according to brain MRI findings. A similar analysis was conducted between hippocampal volume asymmetry and WADA memory score asymmetry (WMA). A Receiver Operating Characteristic (ROC) curve was generated to compare the sensitivity and specificity in predicting successful WADA outcomes based on ipsilateral harmonized normalized hippocampal volumes.ResultsIn patients with mesial temporal sclerosis (MTS), significant positive correlations were found between harmonized normalized hippocampal volumes and ipsilateral WADA memory scores, as well as between harmonized hippocampal volume asymmetries and WMA. However, no significant correlations were found in patients with epileptogenic lesions other than MTS or those with normal brain MRIs. A harmonized normalized hippocampal volume threshold of ≥ 28.94 units was identified as a predictor of a WADA memory score exceeding 50% following contralateral carotid artery injection, with a sensitivity of 62.1% and a specificity of 100%.SignificanceThis study indicates that hippocampal volumetry could potentially serve as an alternative to the WADA test in patients with MTS. Conversely, in individuals with normal MRI results or other types of epileptogenic lesions, hippocampal volumetry does not reliably predict memory deficits, necessitating the use of the WADA test or functional MRI for planning resections of mesial temporal structures in the dominant hemisphere.